Between Dualism and Immanentism Sacramental Ontology and History - Enrico Beltramini (Religions, 2021)
How to deal with religious ideas in religious history (and in history in general) has recently become a matter of discussion. In particular, a number of authors have framed their work around the concept of ‘sacramental ontology,’ that is, a unified vision of reality in which the secular and the religious come together, although maintaining their distinction. The authors’ choices have been criticized by their fellow colleagues as a form of apologetics and a return to integralism. The aim of this article is to provide a proper context in which to locate the phenomenon of sacramental ontology. I suggest considering (1) the generation of the concept of sacramental ontology as part of the internal dialectic of the Christian intellectual world, not as a reaction to the secular; and (2) the adoption of the concept as a protection against ontological nihilism, not as an attack on scientific knowledge.